Patch test results with the European baseline series, 2019/20—Joint European results of the ESSCA and the EBS working groups of the ESCD, and the GEIDAC - Uter, Wolfgang; Wilkinson, S. Mark; Aerts, Olivier; Bauer, Andrea; Borrego, Leopoldo; Brans, Richard; Buhl, Timo; Dickel, Heinrich; Dugonik, Aleksandra; Filon, Francesca Larese; Garcìa, Pedro Mercader; Giménez‐Arnau, Ana; et al. (Contact dermatitis, 2022)
Background Continual analyses of patch test results with the European baseline series (EBS) serve both contact allergy surveillance and auditing the value of included allergens. Objectives To present results of current EBS patch testing, obtained in 53 departments in 13 European countries during 2019 and 2020. Methods Anonymised or pseudonymised individual data and partly aggregated data on demographic/clinical characteristics and patch test rest results with the EBS were prospectively collected and centrally pooled and analysed. Results In 2019 and 2020, 22 581 patients were patch tested with the EBS. Sensitization to nickel remained most common (19.8 [19.2–20.4]% positivity [95% confidence interval]). Fragrance mix I and Myroxylon pereirae yielded very similar results with 6.80 (6.43–7.19)% and 6.62 (6.25–7.00)% positivity, respectively. Formaldehyde at 2% aq. yielded almost one percentage point more positive reactions than 1% concentration (2.49 [2.16–2.85]% vs. 1.59 [1.33–1.88]); methylchloroisothiazolinone/methylisothiazolinone (MCI/MI) and MI alone up to around 5% positives. Among the new additions, propolis was most commonly positive (3.48 [3.16–3.82]%), followed by 2‐hydroxyethyl methacrylate (2.32 [2.0–2.68]%). Conclusion Ongoing surveillance on the prevalence of contact sensitization contributes to an up‐to‐date baseline series containing the most frequent and/or relevant contact sensitizers for routine patch testing in Europe. Top five from 2019 to 2020: nickel 20%, fragrance mix I 7%, Myroxylon pereirae 7%, cobalt 6% and (chloro‐)methylisothiazolinone 5%. Newcomers 2019–2022: propolis 3%, with large geographic variation, 2‐hydroxyethyl methacrylate 2%. Important to test patients with the latest, updated version of the European baseline series.